2016
DOI: 10.1111/jocs.12754
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Subarterial Ventricular Septal Defect Occlusion Using a Minimally Invasive Incision

Abstract: Transthoracic subarterial ventricular septal defect occlusion using a minimally invasive incision may be an alternative to open surgical repair in selected patients. doi: 10.1111/jocs.12754 (J Card Surg 2016;31:398-402).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…They found that in cases with a VSD size > 5 mm, the effective contact area of the occluder became small and, in cases with a VSD size < 5 mm, there was a relatively small opening in the superior margin. Thus, in cases with a VSD size < 5 mm, the device rarely affects the pulmonary valve and is less likely to be displaced from the original position [16]. The incidence of occluder displacement in patients with VSDs > 5 mm was greater than the incidence of displacement in patients with VSDs < 5 mm.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…They found that in cases with a VSD size > 5 mm, the effective contact area of the occluder became small and, in cases with a VSD size < 5 mm, there was a relatively small opening in the superior margin. Thus, in cases with a VSD size < 5 mm, the device rarely affects the pulmonary valve and is less likely to be displaced from the original position [16]. The incidence of occluder displacement in patients with VSDs > 5 mm was greater than the incidence of displacement in patients with VSDs < 5 mm.…”
Section: Discussionmentioning
confidence: 91%
“…Further meta-regression showed that a ratio of occluder size (mm)/weight (kg) above 0.4 was a risk factor for postoperative RSs with a Coef of − 0.28 (95% CI: − 0.49--0.66, p = 0.020). Zhang and his colleagues also reported that procedure-induced aortic regurgitation (AR) was associated with device diameter and patient weight (OR = 12.3 95% CI 1.5-99.2) [16]. Thus, the ratio of occluder size (mm)/weight (kg) below may be another patient selection criterion for perventricular device closure of dcsVSDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 108 articles were written in Chinese 5,12,26–29,31,32,36–43,46,70–132,134–159,174,175 , whereas 58 articles were written in English 4,6,11,25,30,3335,44,45,47–69,133,160163,165173,176186 , and the remaining article was written in Portuguese 164 . All trials were published between 1998 and 2016.…”
Section: Resultsmentioning
confidence: 99%